From theory to practice - Zolak Poljašević, Branka (Naše gospodarstvo, 2024)
Although, in theory, a considerable amount of literature emphasizes the significance of employee incentive pay, there is not much empirical research indicating their dispersion in practice. The primary purpose of this study is to explore the level of implementation of various incentives in three countries: Slovenia, Serbia, Bosnia and Herzegovina. The research was conducted on a sample of 321 companies. Data for this study were extracted from the CRANET dataset. The latest data collection cycle was conducted in 2021-2022. In addition to descriptive statistics, the Pearson Chi-Square Test and Cramer's V test were used to test hypotheses. The research results indicate a statistically significant difference in using most observed compensation elements among the observed countries. The study contributes to compensation management literature by presenting empirical data regarding the degree of implementation of various compensation instruments in three observed countries.
Keywords: Bosna in Hercegovina; compensations; country context; incentives; managers; nadomestila; nagrade; plače; professionals; Slovenija; spodbude; Srbija; strokovnjaki; vodstveni delavci